2022
DOI: 10.1186/s12944-022-01702-1
|View full text |Cite
|
Sign up to set email alerts
|

Replacing saturated fatty acids with polyunsaturated fatty acids increases the abundance of Lachnospiraceae and is associated with reduced total cholesterol levels—a randomized controlled trial in healthy individuals

Abstract: Background Improving dietary fat quality strongly affects serum cholesterol levels and hence the risk of cardiovascular diseases (CVDs). Recent studies have identified dietary fat as a potential modulator of the gut microbiota, a central regulator of host metabolism including lipid metabolism. We have previously shown a significant reduction in total cholesterol levels after replacing saturated fatty acids (SFAs) with polyunsaturated fatty acids (PUFAs). The aim of the present study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…In recent studies, Deng et al found that empagliflozin may provide cardiovascular benefits by altering gut microbiota and plasma metabolites [ 6 ]. Consistently, Telle-Hansen et al showed that replacing saturated fatty acids with polyunsaturated fatty acids altered heart-related the abundance of specific gut microbiota [ 7 ], which improved the prognosis. Several other studies have shown that changes in trimethylamine N-oxide (TMAO) which is produced by gut bacteria, strongly associated with different pathological conditions in the heart, including hypertension and atherosclerosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 94%
“…In recent studies, Deng et al found that empagliflozin may provide cardiovascular benefits by altering gut microbiota and plasma metabolites [ 6 ]. Consistently, Telle-Hansen et al showed that replacing saturated fatty acids with polyunsaturated fatty acids altered heart-related the abundance of specific gut microbiota [ 7 ], which improved the prognosis. Several other studies have shown that changes in trimethylamine N-oxide (TMAO) which is produced by gut bacteria, strongly associated with different pathological conditions in the heart, including hypertension and atherosclerosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 94%
“…FO combined with B. subtilis jzxj-7 improved the abundance of immunity-related bacterial taxa. After 14 days of supplementation, an increase in the abundance of probiotics Faecalibaculum , 38 Bifidobacterium , 39 and Lachnospiraceae NK4B4 40 indicated that FO in combination with B. subtilis jzxj-7 exerted a positive influence for beneficial bacteria to thrive. Furthermore, FO and B. subtilis jzxj-7 suppressed the relative abundance of potential disease biomarker microbes including Muribaculaceae , 41 Staphylococcus , 42 Raoultella , 43 Escherichia – Shigella , 44 and Rikenellaceae , 45 suggesting that FO and B. subtilis jzxj-7 could potentially be a functional food that could prevent pathogen infections.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study in which mice received 60% of energy from fat (mainly lard), a lower amount of Lachnospiraceae was observed after 9 weeks [ 68 ]. Lachnospiraceae appears to be positively associated with unsaturated fat intake and negatively associated with triglycerides and I- t FA exposure [ 69 , 70 ]. Lactobacillus is a group of probiotic bacteria known for their beneficial effects by improving the bioavailability of nutrients [ 71 ].…”
Section: Discussionmentioning
confidence: 99%